The impact of specialization on farm financial performance - Bowman, Whitney (Kansas State University, 2019)
The impact of specialization on farm financial performance depends on the magnitude of economies of size and scope, as well as manager productivity, commodity pricing performance, and producer risk preference. The objective of this study was to investigate the impact of risk and specialization on farm financial performance, specifically on the mean and variance of return on equity. A balanced panel of 459 Kansas farms was created from Kansas Farm Management Association member farms from 2009 through 2018. Four measures of specialization were used in the model: Herfindahl index; crop-livestock and crop-custom work interaction terms; percentage of income from grains and percentage of income from cash crops; and percentage of income from livestock. The impact of specialization and risk on mean financial performance and the impact of specialization on risk were estimated using three-stage least squares regression and two-stage least squares regressions. Variable means and regression coefficients from the three-stage least squares regression were used to calculate financial performance elasticities. Results show specialization is associated with increased mean financial performance and variance in financial performance. Diversifying into both crop and livestock production is associated with decreased mean farm financial performance. Liquidity and financial efficiency were associated with relatively large impacts on mean financial performance, suggesting that effective cost management is associated with higher mean financial performance. Operator age, solvency, and specializing into production of cash crops such as soybeans and cotton were associated with increased variance in financial performance. These findings have implications for farms to better allocate resources to improve returns and manage risk, and for the use of Extension resources in working with farms of different enterprises.
Keywords: Farm management; Agricultural economics; Specialization; Return on equity; Livestock; Crops